Heavy metal curing stabilizer for rare earth tailing treatment and application of heavy metal curing stabilizer
By using heavy metal curing stabilizers composed of granulated blast furnace slag, calcium carbide slag and fly ash, the problem of poor curing effect of heavy metals in rare earth tailings treatment is solved, and the preparation of cured bodies with high strength and low leaching concentration is achieved, which meets the requirements of green development.
Patent Information
- Application Number
- CN202411894659.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-20
- Publication Date
- 2025-03-21
AI Technical Summary
The prior art is difficult to effectively cure heavy metals in rare earth tailings treatment, resulting in environmental pollution and waste of resources. Traditional curing agents have problems such as CO2 emissions, large dry shrinkage, and prone to cracking.
A heavy metal curing stabilizer consisting of granulated blast furnace slag, calcium carbide slag and fly ash is used to optimize the dosage and process flow to prepare high-strength and low leaching concentration rare earth tailings cured bodies to replace traditional cement and liquid alkali exciters.
It has achieved efficient curing of rare earth tailings, improved the compressive strength and stability of the cured body, significantly reduced the leaching concentration of heavy metals, and has the advantages of low energy consumption, low CO2 emissions and low resource consumption, which meets the requirements of green development.
Smart Images

Figure CN119661137A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of tailings treatment, and in particular relates to a heavy metal solidifying stabilizer for rare earth tailings treatment and application thereof. Background Art
[0002] Rare earth tailings, as a type of non-ferrous metal tailings, are the main by-products of rare earth mines after leaching operations and effective extraction of rare earth elements. According to incomplete statistics, light rare earth mines in the north, such as Baosteel Bayan Obo rare earth mine, produce about 2.8 million tons of tailings annually; while the annual tailings of the Yakniuping rare earth mine in Mianning, Sichuan, are about 180,000 tons. For the ionic heavy rare earth mines in the south, due to the low grade of rare earth ore, every ton of rare earth products mined will produce about 1,500 to 2,000 tons of tailings. After years of large-scale mining, the ionic rare earth tailings in the south have piled up into mountains, with a total amount of up to 3 billion tons at present, and are growing at a rate of tens of millions of tons per year. These accumulating tailings usually contain a variety of heavy metal elements, such as lead, zinc, cadmium, arsenic, thallium, etc. These toxic elements remaining in the rare earth tailings are extremely susceptible to erosion and spread by rainwater. If not handled properly, these harmful substances will inevitably cause harm to the ecological environment once they leach into water and soil, and seriously threaten public health and safety. Therefore, formulating reasonable, efficient and safe rare earth tailings treatment measures to reduce or eliminate the environmental risks brought by rare earth tailings and realize the solid waste resource utilization of rare earth tailings has become an important ecological and environmental issue that needs to be urgently addressed.
[0003] At present, solidification / stabilization technology is the most commonly used important technical means in the harmless disposal and comprehensive reuse of tailings. Solidification refers to the process of converting tailings into hard-to-penetrate, stable solidified blocks by adding curing agents such as cementitious materials. Stabilization refers to the process of converting pollutants into difficult-to-dissolve and leaching forms through chemical reactions between stabilizing agents and pollutants. According to the different materials that play a gelling role in the solidification / stabilization technology, the curing stabilizers can be divided into inorganic binders, such as cement, lime, etc.; organic binders, such as thermoplastic materials such as asphalt; thermosetting organic polymers, such as phenolic plastics and epoxides; glassy substances, etc. However, the curing effect of the above-mentioned curing stabilizers on tailings is not ideal. For example, traditional cement-based curing agents such as cement and lime have a certain strength after curing, but they will emit a large amount of CO during curing. 2 , the curing time is long, and it is easy to shrink and crack in the later stage, and the long-term stability is poor. Most of them use liquid alkali activators such as NaOH and water glass, which are inconvenient to transport and have complicated curing process. Curing agents such as asphalt have limited curing range and are usually used to solidify solid waste containing radioactive elements. Curing agents such as epoxides usually need to be used in combination with other curing agents, and the heavy metal leaching concentration after epoxide curing is high. These traditional curing stabilizers seriously limit the reuse of tailings after curing.
[0004] Therefore, it is particularly important to develop a new type of heavy metal solidification stabilizer and its application technology specifically for rare earth tailings treatment. This new type of solidification stabilizer can significantly reduce the leaching concentration of heavy metals while improving the compressive strength of tailings. This is not only of great significance for the safe treatment of rare earth tailings and the secondary development of resources, but also provides an innovative solution for the treatment of other types of heavy metal tailings using solidification / stabilization technology. Summary of the invention
[0005] To solve the above problems, the purpose of the present invention is to provide a heavy metal solidifying stabilizer for rare earth tailings treatment and its application, which makes full use of slag and fly ash to replace cement and lime, and calcium carbide slag to replace liquid alkali activators such as NaOH and water glass, and optimizes the dosage of the curing agent to configure a solidified sample with high strength and good construction performance, saves engineering costs, and improves the utilization rate of solid wastes such as rare earth tailings, blast furnace slag, fly ash, and calcium carbide slag, achieving the purpose of "solid waste utilization and waste treatment", which meets the overall requirements of high-quality green development of my country's non-ferrous metal mining and metallurgical industry.
[0006] An embodiment of the present invention provides a heavy metal solidification stabilizer for rare earth tailings treatment, wherein the heavy metal solidification stabilizer is composed of: Granulated blast furnace slag with a mass fraction of 40% to 60%, carbide slag with a mass fraction of 30% to 50%, and fly ash with a mass fraction of 0% to 10%.
[0007] As some embodiments of the present invention, the granulated blast furnace slag is granulated S105 blast furnace slag, and its specific surface area is 628m 2 / kg, its main chemical components are: CaO: 35.30%, SiO2: 34.50%, Al2O3: 16.70%, SO3: 1.24%, Fe2O3: 1.5%, MgO: 5.01%, and Loss: 3.55%.
[0008] Wherein, Loss means loss on ignition, which is the percentage of the mass lost after ignition for a sufficiently long time under certain high temperature conditions to the mass of the original sample. Loss on ignition (Loss on ignition), in the present invention, refers to the raw material that has been dried in the temperature range of 105°C to 110°C to lose external moisture, and the percentage of the mass lost after ignition for a sufficiently long time under certain high temperature conditions to the mass of the original sample.
[0009] As some embodiments of the present invention, the main chemical components of carbide slag are: CaO is 75.3%, MgO is 1.4%, acid insoluble matter is 2.55%, and Loss is 20.75%.
[0010] As some embodiments of the present invention, the fly ash is Class II fly ash, and its main chemical components are: SiO2 is 48.85%, Al2O3 is 35.72%, Fe2O3 is 4.33%, MgO is 0.86%, K2O is 0.70%, Na2O is 0.33%, TiO2 is 1.37%, P2O5 is 0.37%, and Loss is 3.02%.
[0011] As preferred in some embodiments of the present invention, the mass fraction of granulated blast furnace slag is 45%.
[0012] As preferred in some embodiments of the present invention, the mass fraction of carbide slag is 45%.
[0013] As preferred in some embodiments of the present invention, the mass fraction of fly ash is 10%.
[0014] Another aspect of the present invention provides an application of the heavy metal solidification stabilizer for rare earth tailings treatment as described above, and the application method is as follows: Step 1: After drying the rare earth tailings, the rare earth tailings are put into a jaw crusher for crushing to obtain rare earth tailings fragments; Step 2: Put the rare earth tailings produced by the crusher into a vibrating screen to vibrate and sieve to obtain rare earth tailings particles with a particle size less than 2 mm.
[0015] Step 3: pouring the rare earth tailing particles and 0.05 to 0.15 times the mass of the heavy metal solidifying stabilizer into a planetary cement mortar mixer, and dry-mixing at a low speed to form a dry-mixed mixture of the rare earth tailings and the heavy metal solidifying stabilizer; Step 4: injecting 0.4 times the mass of the dry-mixed mixture of the rare earth tailings and the heavy metal solidifying stabilizer into a planetary cement mortar mixer, and stirring evenly to form a fluid slurry; Step 5: Fix the mold on a vibration table, fill the fluid slurry into the mold in three layers and tamp them, tamp each layer from the edge to the middle, and vibrate it on the vibration table to form it, scrape the surface flat and cover it with plastic wrap; Step six: Place the prepared sample in a standard curing room, and under the curing conditions of a temperature of 15°C to 25°C and a relative humidity of 94% to 98%, cure it in a mold for 18h to 36h and then demold it. After demolding, continue to cure it in the standard curing room to the predetermined age to obtain a solidified rare earth tailings body.
[0016] As preferred embodiments of some embodiments of the present invention, in step 1, the drying temperature of the rare earth tailings is 105° C., and the feeding speed into the jaw crusher is 30 kg / min.
[0017] As preferred embodiments of some embodiments of the present invention, in step three, the mass ratio of rare earth tailing particles to heavy metal solidifying stabilizer is 1:0.1.
[0018] As preferred in some embodiments of the present invention, in step three, the low-speed dry mixing time is 2 minutes.
[0019] As preferred in some embodiments of the present invention, in step 4, the stirring time is 15 minutes.
[0020] As some embodiments of the present invention, in step five, the mold is cylindrical.
[0021] As preferred in some embodiments of the present invention, the inner diameter of the cylindrical mold is 50 mm and the height is 100 mm.
[0022] As a preference of some embodiments of the present invention, in step six, the temperature of the standard curing room is 20° C., the relative humidity is 96%, and the mold curing time is 24 hours.
[0023] As some embodiments of the present invention, in step six, the predetermined ages are 7 days and 28 days.
[0024] Compared with the prior art, the present invention can bring the following beneficial effects: 1) The heavy metal solidification stabilizer for rare earth tailings treatment provided by the present invention and its application can alleviate the ecological environment problems caused by the large amount of rare earth tailings accumulation, and can also improve the utilization rate of solid wastes such as granulated blast furnace slag, carbide slag, and fly ash.
[0025] 2) The heavy metal solidifying stabilizer and its application for rare earth tailings treatment of the present invention fully utilizes the characteristics of alkali-activated slag hydration and gelation, and the obtained partial rare earth tailings solidified body has a compressive strength of up to 3.6MPa after curing for 7 days. In addition, the present invention uses slag and fly ash to replace cement and lime, which makes up for the shortcomings of large shrinkage and easy cracking of traditional cement-based solidified bodies, and effectively reduces the use of cement; the present invention also uses carbide slag as an alkali activator to replace liquid alkali activators such as NaOH and water glass, and the prepared solidifying stabilizer is a solidifying stabilizer composed of all solid waste. Compared with traditional solidifying stabilizers, the present invention has the advantages of convenient storage and transportation and simple solidification process. While reducing the concentration of heavy metal leaching and improving the strength of the solidified body, it has the advantages of low energy consumption, low CO2 emissions, and low resource consumption, and has significant economic, environmental and social benefits.
[0026] 3) The present invention fully considers the promoting effect of surface water, groundwater infiltration and environmental pH fluctuation, such as floods, acid rain, etc., on the migration of heavy metal elements such as Pb and Zn in rare earth tailings when rare earth tailings are stored or used in backfilling and pouring of rare earth mining areas, subsidence areas, foundation pits and fertilizer tanks. These heavy metal elements with migration risks are restricted in the solidified body by using a solidifying stabilizer, so that the solidified body has the ability to resist long-term natural environmental changes. After solidification, the leaching toxicity content of Pb and Zn in the rare earth tailings is lower than 2.5 mg / L, and the heavy metal fixation efficiency can reach more than 97%, which meets the solid waste toxicity leaching standard, effectively reduces environmental risks, and provides a solution for the safe disposal and secondary utilization of rare earth tailings. BRIEF DESCRIPTION OF THE DRAWINGS
[0027] In order to more clearly illustrate the specific implementation of the present invention or the technical solution in the prior art, the drawings required for describing the specific implementation or the prior art will be briefly introduced below. Obviously, the drawings described below are only one implementation of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative work.
[0028] Figure 1 A photo of rare earth tailings treated by an embodiment of the present invention; Figure 2 This is a photo of rare earth tailing particles obtained by crushing in Example 1 of the present invention; Figure 3 This is a photo of the heavy metal curing stabilizer prepared in Example 1 of the present invention; Figure 4 It is a structural schematic diagram of a mold in an embodiment of the present invention; Figure 5 This is a photo of the rare earth tailings solidified body prepared in Example 1 of the present invention. DETAILED DESCRIPTION
[0029] In order to make the purpose, technical scheme and beneficial effects of the present invention clearer and more specific, the embodiments and experimental examples of the present invention will be described below to further explain the present invention in detail. It should be noted that the embodiments described below are only some typical examples of the present invention, rather than all implementation methods of the present invention. Various modifications, replacements and deformations based on the embodiments of the present invention made by ordinary technicians in this field without making creative work all fall within the protection scope of the present invention.
[0030] In the present invention: rare earth tailings are taken from Ganzhou, Jiangxi (such as Figure 1As shown), according to the "Solid Waste - Leaching Toxicity Leaching Method Sulfuric Acid and Nitric Acid Method" (HJ / T299-2007), a toxicity leaching test was carried out on the rare earth tailings to obtain a rare earth tailings leachate. The lead content in the rare earth tailings leachate was measured by inductively coupled plasma emission spectrometry to be 86 mg / L and the zinc content was 190 mg / L; the mold specification in the embodiment of the present invention is a cylinder with an inner diameter of 50 mm and a height of 100 mm (as shown Figure 4 as shown).
[0031] Unless otherwise specified, all raw material components in the following examples can be purchased from commercial sources, the experimental instruments used are conventional laboratory instruments, and the performance testing methods are known testing methods in the art.
[0032] Example 1: This example first provides a heavy metal solidification stabilizer for rare earth tailings treatment, such as Figure 3 As shown, including: 45% by mass of granulated blast furnace slag, 45% by mass of carbide slag, and 10% by mass of fly ash.
[0033] In this embodiment, the granulated blast furnace slag is granulated S105 blast furnace slag, and its specific surface area is 628m 2 / kg, its main chemical components are: CaO is 35.30%, SiO2 is 34.50%, Al2O3 is 16.70%, SO3 is 1.24%, Fe2O3 is 1.5%, MgO is 5.01%, and Loss is 3.55%; The main chemical components of carbide slag are: CaO 75.3%, MgO 1.4%, acid insoluble matter 2.55%, and Loss 20.75%; The fly ash used is grade II fly ash, and its main chemical components are: SiO2 is 48.85%, Al2O3 is 35.72%, Fe2O3 is 4.33%, MgO is 0.86%, K2O is 0.70%, Na2O is 0.33%, TiO2 is 1.37%, P2O5 is 0.37%, and Loss is 3.02%.
[0034] This embodiment also provides an application method of the heavy metal solidification stabilizer for rare earth tailings treatment, the specific steps are: Step 1: drying the rare earth tailings at 105° C., and then feeding them into a jaw crusher at a feeding rate of 30 kg / min to crush them to obtain rare earth tailings crushed materials; Step 2: Put the crushed material from the crusher into a vibrating screen and vibrate it. The aperture of the vibrating screen is set to 2mm to obtain rare earth tailing particles with a particle size of less than 2mm (such as Figure 2 shown); Step 3: Pour 1080g of rare earth tailing particles and 108g of heavy metal solidifying stabilizer into a planetary cement mortar mixer and dry mix at low speed for 2 minutes to prepare a dry mixture of rare earth tailings and heavy metal solidifying stabilizer (the mass ratio of rare earth tailings to heavy metal solidifying stabilizer is 1:0.1); Step 4: inject 0.4 times the mass of the dry-mixed mixture of the rare earth tailings and the heavy metal solidifying stabilizer into a planetary cement mortar mixer, and stir for 15 minutes until uniform to prepare a fluid slurry; Step 5: Fix a cylindrical mold with an inner diameter of 50 mm and a height of 100 mm on a vibration table, fill the fluid slurry into the mold in three layers and tamp it, tamp each layer from the edge to the middle, and vibrate it on the vibration table to form it, scrape the surface flat and cover it with plastic wrap; Step 6: Place the prepared sample in a standard curing room, and under the curing conditions of a temperature of 20°C and a relative humidity of 96%, curing it in a mold for 24 hours before demolding it. After demolding, continue curing in the standard curing room to a predetermined age to obtain a rare earth tailings solidified body (such as Figure 5 as shown).
[0035] Example 2: This example first provides a heavy metal solidification stabilizer for rare earth tailings treatment, comprising: 50% by mass of granulated blast furnace slag and 50% by mass of calcium carbide slag.
[0036] In this embodiment, the granulated blast furnace slag is granulated S105 blast furnace slag, and its specific surface area is 628m 2 / kg, its main chemical components are: CaO is 35.30%, SiO2 is 34.50%, Al2O3 is 16.70%, SO3 is 1.24%, Fe2O3 is 1.5%, MgO is 5.01%, and Loss is 3.55%; The main chemical components of carbide slag are: CaO is 75.3%, MgO is 1.4%, acid insoluble matter is 2.55%, and Loss is 20.75%.
[0037] This embodiment also provides an application method of the heavy metal solidification stabilizer for rare earth tailings treatment, the specific steps are: Step 1: drying the rare earth tailings at 105° C., and then feeding them into a jaw crusher at a feeding rate of 30 kg / min to crush them to obtain rare earth tailings crushed materials; Step 2: Put the crushed material produced by the crusher into a vibrating screen for vibrating, and set the aperture of the vibrating screen to 2 mm to obtain rare earth tailing particles with a particle size less than 2 mm; Step 3: Pour 1080g of rare earth tailing particles and 108g of heavy metal solidifying stabilizer into a planetary cement mortar mixer and dry mix at low speed for 2 minutes to prepare a dry mixture of rare earth tailings and heavy metal solidifying stabilizer (the mass ratio of rare earth tailings to heavy metal solidifying stabilizer is 1:0.1); Step 4: inject 0.4 times the mass of the dry-mixed mixture of the rare earth tailings and the heavy metal solidifying stabilizer into a planetary cement mortar mixer, and stir for 15 minutes until uniform to prepare a fluid slurry; Step 5: Fix a cylindrical mold with an inner diameter of 50 mm and a height of 100 mm on a vibration table, fill the fluid slurry into the mold in three layers and tamp it, tamp each layer from the edge to the middle, and vibrate it on the vibration table to form it, scrape the surface flat and cover it with plastic wrap; Step 6: Place the prepared sample in a standard curing room, and under the curing conditions of a temperature of 20°C and a relative humidity of 96%, demold the sample after curing for 24 hours. After demolding, continue curing in the standard curing room to the predetermined age to obtain a solidified rare earth tailings body.
[0038] Example 3: This example first provides a heavy metal solidification stabilizer for rare earth tailings treatment, comprising: 60% by mass of granulated blast furnace slag, 30% by mass of carbide slag, and 10% by mass of fly ash.
[0039] Among them, the granulated blast furnace slag is granulated S105 blast furnace slag, and its specific surface area is 628m 2 / kg, its main chemical components are: CaO is 35.30%, SiO2 is 34.50%, Al2O3 is 16.70%, SO3 is 1.24%, Fe2O3 is 1.5%, MgO is 5.01%, and Loss is 3.55%; The main chemical components of carbide slag are: CaO 75.3%, MgO 1.4%, acid insoluble matter 2.55%, and Loss 20.75%; The fly ash used is grade II fly ash, and its main chemical components are: SiO2 is 48.85%, Al2O3 is 35.72%, Fe2O3 is 4.33%, MgO is 0.86%, K2O is 0.70%, Na2O is 0.33%, TiO2 is 1.37%, P2O5 is 0.37%, and Loss is 3.02%.
[0040] This embodiment also provides an application method of the heavy metal solidification stabilizer for rare earth tailings treatment, the specific steps are: Step 1: drying the rare earth tailings at 105° C., and then feeding them into a jaw crusher at a feeding rate of 30 kg / min to crush them to obtain rare earth tailings crushed materials; Step 2: Put the crushed material from the crusher into a vibrating screen and vibrate it. The aperture of the vibrating screen is set to 2mm to obtain rare earth tailing particles with a particle size of less than 2mm. Step 3: Pour 1080g of rare earth tailing particles and 108g of heavy metal solidifying stabilizer into a planetary cement mortar mixer and dry mix at low speed for 2 minutes to prepare a dry mixture of rare earth tailings and heavy metal solidifying stabilizer (the mass ratio of rare earth tailings to heavy metal solidifying stabilizer is 1:0.1); Step 4: inject 0.4 times the mass of the dry-mixed mixture of the rare earth tailings and the heavy metal solidifying stabilizer into a planetary cement mortar mixer, and stir for 15 minutes until uniform to prepare a fluid slurry; Step 5: Fix a cylindrical mold with an inner diameter of 50 mm and a height of 100 mm on a vibration table, fill the fluid slurry into the mold in three layers and tamp it, tamp each layer from the edge to the middle, and vibrate it on the vibration table to form it, scrape the surface flat and cover it with plastic wrap; Step 6: Place the prepared sample in a standard curing room, and under the curing conditions of a temperature of 20°C and a relative humidity of 96%, demold the sample after curing for 24 hours. After demolding, continue curing in the standard curing room to the predetermined age to obtain a solidified rare earth tailings body.
[0041] Example 4: This example first provides a heavy metal solidification stabilizer for rare earth tailings treatment, comprising: 45% by mass of granulated blast furnace slag, 45% by mass of carbide slag, and 10% by mass of fly ash.
[0042] Among them, the granulated blast furnace slag is granulated S105 blast furnace slag, and its specific surface area is 628m 2 / kg, its main chemical components are: CaO is 35.30%, SiO2 is 34.50%, Al2O3 is 16.70%, SO3 is 1.24%, Fe2O3 is 1.5%, MgO is 5.01%, and Loss is 3.55%; The main chemical components of carbide slag are: CaO 75.3%, MgO 1.4%, acid insoluble matter 2.55%, and Loss 20.75%; The fly ash used is grade II fly ash, and its main chemical components are: SiO2 is 48.85%, Al2O3 is 35.72%, Fe2O3 is 4.33%, MgO is 0.86%, K2O is 0.70%, Na2O is 0.33%, TiO2 is 1.37%, P2O5 is 0.37%, and Loss is 3.02%.
[0043] This embodiment also provides an application method of the heavy metal solidification stabilizer for rare earth tailings treatment, the specific steps are: Step 1: drying the rare earth tailings at 105° C., and then feeding them into a jaw crusher at a feeding rate of 30 kg / min to crush them to obtain rare earth tailings crushed materials; Step 2: Put the crushed material from the crusher into a vibrating screen and vibrate it. The aperture of the vibrating screen is set to 2mm to obtain rare earth tailing particles with a particle size of less than 2mm. Step 3: Pour 1080g of rare earth tailing particles and 54g of heavy metal solidifying stabilizer into a planetary cement mortar mixer and dry mix at low speed for 2 minutes to prepare a dry mixture of rare earth tailings and heavy metal solidifying stabilizer (the mass ratio of rare earth tailings to heavy metal solidifying stabilizer is 1:0.05); Step 4: inject 0.4 times the mass of the dry-mixed mixture of the rare earth tailings and the heavy metal solidifying stabilizer into a planetary cement mortar mixer, and stir for 15 minutes until uniform to prepare a fluid slurry; Step 5: Fix a cylindrical mold with an inner diameter of 50 mm and a height of 100 mm on a vibration table, fill the fluid slurry into the mold in three layers and tamp it, tamp each layer from the edge to the middle, and vibrate it on the vibration table to form it, scrape the surface flat and cover it with plastic wrap; Step 6: Place the prepared sample in a standard curing room, and under the curing conditions of a temperature of 20°C and a relative humidity of 96%, demold the sample after curing for 24 hours. After demolding, continue curing in the standard curing room to the predetermined age to obtain a solidified rare earth tailings body.
[0044] Example 5: This example first provides a heavy metal solidification stabilizer for rare earth tailings treatment, comprising: 45% by mass of granulated blast furnace slag, 45% by mass of carbide slag, and 10% by mass of fly ash.
[0045] Among them, the granulated blast furnace slag is granulated S105 blast furnace slag, and its specific surface area is 628m 2 / kg, its main chemical components are: CaO is 35.30%, SiO2 is 34.50%, Al2O3 is 16.70%, SO3 is 1.24%, Fe2O3 is 1.5%, MgO is 5.01%, and Loss is 3.55%; The main chemical components of carbide slag are: CaO 75.3%, MgO 1.4%, acid insoluble matter 2.55%, and Loss 20.75%; The fly ash used is grade II fly ash, and its main chemical components are: SiO2 is 48.85%, Al2O3 is 35.72%, Fe2O3 is 4.33%, MgO is 0.86%, K2O is 0.70%, Na2O is 0.33%, TiO2 is 1.37%, P2O5 is 0.37%, and Loss is 3.02%.
[0046] This embodiment also provides an application method of the heavy metal solidification stabilizer for rare earth tailings treatment, the specific steps are: Step 1: drying the rare earth tailings at 105° C., and then feeding them into a jaw crusher at a feeding rate of 30 kg / min to crush them to obtain rare earth tailings crushed materials; Step 2: Put the crushed material from the crusher into a vibrating screen and vibrate it. The aperture of the vibrating screen is set to 2mm to obtain rare earth tailing particles with a particle size of less than 2mm. Step 3: Pour 1080g of rare earth tailings particles and 162g of heavy metal solidifying stabilizer into a planetary cement mortar mixer and dry mix at low speed for 2 minutes to prepare a dry mixture of rare earth tailings and heavy metal solidifying stabilizer (the mass ratio of rare earth tailings to heavy metal solidifying stabilizer is 1:0.15); Step 4: inject 0.4 times the mass of the dry-mixed mixture of the rare earth tailings and the heavy metal solidifying stabilizer into a planetary cement mortar mixer, and stir for 15 minutes until uniform to prepare a fluid slurry; Step 5: Fix a cylindrical mold with an inner diameter of 50 mm and a height of 100 mm on a vibration table, fill the fluid slurry into the mold in three layers and tamp it, tamp each layer from the edge to the middle, and vibrate it on the vibration table to form it, scrape the surface flat and cover it with plastic wrap; Step 6: Place the prepared sample in a standard curing room, and under the curing conditions of a temperature of 20°C and a relative humidity of 96%, demold the sample after curing for 24 hours. After demolding, continue curing in the standard curing room to the predetermined age to obtain a solidified rare earth tailings body.
[0047] In order to further confirm the effect of the heavy metal solidification stabilizer of the present invention and the solidification and stabilization effect of the rare earth tailings solidified body prepared by the method of the present invention on heavy metals, the rare earth tailings solidified bodies prepared in the above Examples 1 to 5 were tested in this specific implementation: Test Example 1: In this test example, the compressive strength of the rare earth tailings solidified bodies prepared in Examples 1 to 5 was tested.
[0048] The test method refers to the method for determining the compressive strength of cement mortar in GB / T17671-2021 "Test Method for Strength of Cement Mortar", and the compressive strength test of the prepared rare earth tailings solidified body is carried out. The test results are shown in Table 1.
[0049] Table 1 Compressive strength test table of rare earth tailings solidification
[0050] It can be seen from the data in Table 1 that the rare earth tailings solidified body obtained in the above embodiments has good compressive strength. By comparing the compressive strength test results of Examples 1, 2, and 3, it can be seen that the rare earth tailings solidified body obtained by the heavy metal solidifying stabilizer ratio in Example 1 has higher compressive strength than that in Example 2 and Example 3. The compressive strength of the rare earth tailings solidified body obtained in Example 1 after curing for 7 days is 1.960 MPa, which is 1.14 times that of Example 2 and 1.03 times that of Example 3; By comparing the compressive strength test results of Examples 1, 4, and 5, It can be seen from the results that when the heavy metal solidifying stabilizer is a mixture of 45% by mass of granulated blast furnace slag, 45% by mass of carbide slag, and 10% by mass of fly ash, and the mass ratio of rare earth tailings to heavy metal solidifying stabilizer is 1:(0.05-0.15), the compressive strength of the rare earth tailings solidified body increases with the increase of the dosage of the heavy metal solidifying stabilizer. When the mass ratio of rare earth tailings to heavy metal solidifying stabilizer is 1:0.15, the compressive strength after curing for 7 days is as high as 3.623 MPa, which is 1.85 times that of Example 1 and 6.59 times that of Example 4.
[0051] Test Example 2: In this test example, toxicity leaching tests were carried out on the rare earth tailings solid bodies obtained in Examples 1 to 5 respectively according to "Solid Waste - Leaching Toxicity Leaching Method Sulfuric Acid and Nitric Acid Method" (HJ / T299-2007), and the obtained leachates were tested according to inductively coupled plasma emission spectrometry, and the lead and zinc contents of the rare earth tailings solid body leachates in each example were measured, that is, the contents of the most mobile lead and zinc in the rare earth tailings solid body.
[0052] Table 2 Toxicity leaching test table of rare earth tailings solidification
[0053] As can be seen from the data in Table 2, the total content of mobile lead and zinc elements in the rare earth tailings solidified bodies obtained in Examples 1 to 5 of the present invention is significantly reduced. When the curing is 7 days, the toxic leaching content of Pb and Zn is less than 2.5 mg / L, and the heavy metal fixation efficiency can reach more than 97%, which meets the limit values specified in the "Hazardous Solid Waste Identification Standard-Leaching Toxicity Identification" (GB 5085.3-2007) (Pb<5mg / L, Zn<100mg / L). This shows that the heavy metal solidification stabilizer and its application for rare earth tailings treatment of the present invention can effectively fix the mobile heavy metal elements in rare earth tailings.
[0054] Combining the data in Tables 1 and 2, it can be seen that the present invention can obtain a solidified body with high strength and low heavy metal leaching rate. Compared with Examples 2 and 3, the rare earth tailings solidified body obtained by the heavy metal solidifying stabilizer ratio for rare earth tailings treatment and its application in Example 1 has higher compressive strength and lower heavy metal leaching concentration, which can replace the use of cement and lime, make up for the shortcomings of traditional cement-based solidified bodies such as large shrinkage and easy cracking, and achieve long-term stability of rare earth tailings.
[0055] In addition, the present invention utilizes carbide slag as an alkali activator to replace liquid alkali activators such as NaOH and water glass, and formulates a solidifying stabilizer composed of all solid waste, thereby achieving the purpose of "solid waste utilization and waste treatment with waste", and meeting the overall requirements for high-quality green development of my country's non-ferrous metal mining and metallurgical industry. Compared with traditional solidifying stabilizers, the present invention has a wide source of raw materials, convenient storage and transportation, and a simple solidification process, and has broad application prospects in the harmless disposal of tailings and resource utilization of solid waste.
[0056] The above description is only a preferred embodiment of the present invention, and does not limit the patent scope of the present invention. It is impossible to list all implementation methods here. Any modification, equivalent replacement and improvement made within the spirit and principle of the present invention should be included in the protection scope of the present invention.
[0057] In addition, it should be understood that although the present specification is described according to various implementation methods, not every implementation method contains only one independent technical solution. This narrative method of the specification is only for the sake of clarity. Those skilled in the art should regard the specification as a whole. The technical solutions in each implementation method may also be appropriately combined to form other implementation methods that can be understood by those skilled in the art.
Claims
1. A heavy metal solidification stabilizer for rare earth tailings treatment, characterized in that: Its composition is: Granulated blast furnace slag with a mass fraction of 40% to 60%, carbide slag with a mass fraction of 30% to 50%, and fly ash with a mass fraction of 0% to 10%.
2. The heavy metal solidification stabilizer for rare earth tailings treatment according to claim 1, characterized in that: The granulated blast furnace slag is granulated S105 blast furnace slag, and its specific surface area is 628m 2 / kg, its main chemical components are: CaO: 35.30%, SiO2: 34.50%, Al2O3: 16.70%, SO3: 1.24%, Fe2O3: 1.5%, MgO: 5.01%, and Loss: 3.55%.
3. The heavy metal solidification stabilizer for rare earth tailings treatment according to claim 1, characterized in that: The main chemical components of the carbide slag are: CaO is 75.3%, MgO is 1.4%, acid insoluble matter is 2.55%, and Loss is 20.75%.
4. The heavy metal solidification stabilizer for rare earth tailings treatment according to claim 1, characterized in that: The fly ash is Grade II fly ash, and its main chemical components are: SiO2 is 48.85%, Al2O3 is 35.72%, Fe2O3 is 4.33%, MgO is 0.86%, K2O is 0.70%, Na2O is 0.33%, TiO2 is 1.37%, P2O5 is 0.37%, and Loss is 3.02%.
5. A heavy metal solidification stabilizer for rare earth tailings treatment according to claim 1 or 2, characterized in that: The mass fraction of the granulated blast furnace slag is 45%.
6. A heavy metal solidification stabilizer for rare earth tailings treatment according to claim 1 or 3, characterized in that: The mass fraction of the carbide slag is 45%.
7. A heavy metal solidification stabilizer for rare earth tailings treatment according to claim 1 or 4, characterized in that: The mass fraction of the fly ash is 10%.
8. An application of a heavy metal solidifying stabilizer for rare earth tailings treatment as claimed in any one of claims 1 to 7, characterized in that: The application method is as follows: Step 1: After the rare earth tailings are dried, they are put into a jaw crusher for crushing to obtain rare earth tailings fragments; Step 2: Put the rare earth tailings produced by the crusher into a vibrating screen machine for vibrating, and set the aperture of the vibrating screen machine to 2 mm to obtain rare earth tailings particles with a particle size less than 2 mm; Step 3: pouring the rare earth tailing particles and 0.05 to 0.15 times the mass of the heavy metal solidifying stabilizer into a planetary cement mortar mixer, and dry-mixing at a low speed to form a dry-mixed mixture of the rare earth tailings and the heavy metal solidifying stabilizer; Step 4: injecting 0.4 times the mass of the dry-mixed mixture of the rare earth tailings and the heavy metal solidifying stabilizer into a planetary cement mortar mixer, and stirring evenly to form a fluid slurry; Step 5: Fix the mold on a vibration table, fill the fluid slurry into the mold in three layers and tamp them, tamp each layer from the edge to the middle, and vibrate it on the vibration table to form it, scrape the surface flat and cover it with plastic wrap; Step six: Place the prepared sample in a standard curing room, and under the curing conditions of a temperature of 15°C to 25°C and a relative humidity of 94% to 98%, cure it in a mold for 18h to 36h and then demold it. After demolding, continue to cure it in the standard curing room to the predetermined age to obtain a solidified rare earth tailings body.
9. The use of a heavy metal solidification stabilizer for rare earth tailings treatment according to claim 8, characterized in that: In step 1, the drying temperature of the rare earth tailings is 105°C, and the feeding speed into the jaw crusher is 30kg / min; In step 3, the mass ratio of rare earth tailing particles to heavy metal solidifying stabilizer is 1:0.1; In step six, the temperature of the standard curing room is 20°C, the relative humidity is 96%, and the mold curing time is 24 hours.
10. The use of a heavy metal solidifying stabilizer for rare earth tailings treatment according to claim 9, characterized in that: In step 3, the low-speed dry mixing time is 2 minutes; In step 4, the stirring time is 15 min; In step 5, the mold is cylindrical with an inner diameter of 50 mm and a height of 100 mm; In step six, the predetermined ages are 7 days and 28 days.